Identification of Factors Caused The Risk of Time Delays in The Pulogadung - Widiyanto Nugroho, Anwar; Tukiyo, Tukiyo; Fithra, Herman (International Journal of Engineering, Science and Information Technology, 2022)
To provide livable housing for the residents of DKI Jakarta, especially in urban areas with minimal land availability, the DKI Jakarta Provincial Government supports the development of vertical housing to offset the high demand for housing and limited land. Through the Department of Public Housing and Settlement Areas, the Provincial Government of DKI Jakarta is implementing the Pulogadung-East Jakarta PIK Flats Construction Project. When this research was carried out, the Pulogadung-East Jakarta PIK Flats Construction Project was entering week 63, with work progress reaching 47.689% of the planned 48.725%, or in other words, this project experienced a delay of 1.036% of the scheduled. Therefore, it is necessary to conduct research that aims to identify the factors that cause the risk of time delays, analyze the most dominant factors that lead to the risk of time delays, and look for the necessary handling actions so that the risk of time delays that occur does not increase or can also be prevented or resolved. In this study, the descriptive quantitative method is carried out by surveys, interviews, and distributing questionnaires to respondents. The risk rating was analyzed using MS. Excel is based on a probability and impact matrix, which aims to determine variables with a high level of risk, then expert validation is carried out regarding risk management. And from the analysis results obtained, six variables that cause the risk of time delays in the Pulogadung-East Jakarta PIK Flats Development Project work can occur, namely Late Payment of Term by Owner, Design Changes, Lack of Coordination While Working, Inaccuracy of Material Order, Time, Limited Material Availability in the Market, and the Occurrence of the Corona Outbreak (Covid 19). The results of expert recommendations for the six variables can be expressed in handling actions.